Use of impact-range performance and asymmetry analyses to improve OTA website quality. (March 2016) - Ye, Ben Haobin; Fu, Hui; Law, Rob
Abstract: Over the past decade, China has experienced a rapid growth in tourism. An increasing number of clients are booking tourism products, such as hotel rooms and airline tickets, through local online travel agents (OTAs). OTA websites are also becoming an important part of the Chinese tourism market. However, academic research on how Chinese tourists evaluate and perceive the different attributes of OTAs remains limited. The current study uses impact-range performance and asymmetry analyses, which are improved versions of importance-performance analysis, to examine how customers evaluate OTAs. Results of a questionnaire survey of 289 Chinese respondents reveal the performance of different website attributes, their different levels of impact on customer satisfaction, and the probability that they will generate satisfaction or dissatisfaction. Findings also suggest that the managers of OTA websites should focus on dimensions of customer relations. The theoretical and practical implications of these findings are discussed.